Analisis Leverage Terhadap Profitabilitas Perusahaan Studi Kasus Pada PT. Tambang Batu Bara Bukit Asam Tbk dan PT. Aneka Tambang, Tbk - Supriadi, Yoyon (STIE Kesatuan, 2010)
Leverage is the using of fund sources aside from equity, or in other words, the company makes use of debt where it (the company) will bear constant responsibility. Profitability is the companyâs ability to yield profit. The objective of this research is to find out the influence and the correlation of leverage (X) on profitability (Y) at PT Tambang Batu Bara Bukit Asam (Persero) Tbk. and PT Aneka Tambang Tbk. in the period of 2004 â 2009. The leverage done by the author isDER (Debt to Equity Ratio), whereas for profitability he utilizes ROE (Return on Equity). Analysis method used is common size analysis, that is horizontal common size and vertical common size; and the test is by SPSS 12.0, that is correlation coefficient, determination coefficient, regression coefficient. Itâs obtained that signification result is 48,3%, higher than 10%, so DER (Debt to Equality Ratio) does not have significant correlation towards ROE (Return on Equity). ROE (Return on Equity) is more affected separately by long term debt and equity for PT Tambang Batu Bara Bukit Asam (Persero) Tbk.; whereas for PT Aneka TambangTbk., itâs more affected by total debt.